Potensi Wisata Alam Bumi Perkemahan Lamping Kidang di Desa Cisantana Kabupaten Kuningan - Bariyah, Diah Khoirul; Fadjarajani, Siti; Darmawan, Cahya (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
Kuningan Regency has interesting tourism potential to visit, one of which is the natural tourism of the Lamping Kidang Camping Grounds. This study aims to explore the potential of natural tourism in the Lamping Kidang Camping Grounds, which is located in Cisantana Village, Cigugur District, Kuningan Regency, West Java. Through a literature study approach, this study examines various factors that support the development of the area as a sustainable natural tourism destination. The results of the study indicate that the Lamping Kidang Camping Grounds has various natural attractions, including beautiful mountain views, biodiversity, and adequate facilities, and the tourism of this Camping Grounds includes educational tours of dairy farms, where tourists can try to milk their own cows. Active participation of local communities in the management and provision of tourism services is an important key to the success of the development of this destination. In addition, environmental education and nature conservation programs are expected to increase environmental awareness and support the curiosity of an area. To maximize the potential of natural tourism in the Lamping Kidang Camping Grounds, a sustainable development strategy is needed. This includes improving infrastructure, empowering local communities, environmental conservation, and effective promotion. Diversification of thematic tourism such as eco-tourism and agro-tourism also offers great opportunities to attract various segments of tourists